Relationship between ACTN3 R577X polymorphism and maximal power output in elite Polish athletes - Orysiak, J.; Busko, K.; Michalski, R.; Mazur-Rózycka, J.; Gajewski, J.; Malczewska-Lenczowska, J.; Sitkowski, D.; Pokrywka, A. (Medicina, 2014)
The main purpose of this study was to examine the association between ACTN3 R577X polymorphism and the ability to produce peak power in young male athletes from various sports. Our hypothesis was that the ACTN3 R577X polymorphism is associated with jumping performance and athletes with RR genotype have better scores in tests than athletes with XX or RX genotype independently of the sport discipline.